THE ANALYSIS OF DISTRIBUTOR CHARACTERISTICS, CORPORATE SUPPORT, AND LEARNING ORGANIZATION IN PT. MAHAKARYA SEJAHTERA INDONESIA MANADO DISTRIBUTOR - Gantar, Fedrico Saputra Daymand; Tielung, Maria V.J. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: In the business of multilevel marketing (MLM), the role of distributor is necessary for the effectiveness of business activities. Therefore, the performance of the distributor becomes an important thing. Distributors must have a strong passion in running a business, get support from the company, and organizational learning that can support distributor skills. This study aims to analyze the influence of distributor characteristics, corporate support, and learning organization to improve distributor performance at Distributor of PT. Mahakarya Sejahtera Indonesia Manado. This study uses Quantitative research method by using multiple regression analysis with the number of samples taken in this study as many as 60 respondents as a member of PT. Mahakarya Sejahtera Indonesia Manado Distributor under Meilany Deisy Rengkung, SE. The results showed that the distributor characteristics, corporate support, and learning organization influenced the performance distributors. Distributor characteristics affect the distributor performance. Corporate support has no effect on distributor performance. Learning organization affects the performance distributors. Future research will be better if the population is taken from several groups because it does not rule out the possibility of each group having different habits in its role as a distributor.Keywords: distributor characteristics, corporate support, learning organization, distributor performance.